Investigation of Microbial Contamination Rates of Hospital Equipment and Nosocomial Infection in Different Wards of Two Public Hospitals in Sistan and Balouchestan Province during the First Six Months of 1394 (20 Mars - 20 September 2015) - Zahra Ebrahimi Rigi Tanha (Journal of Global Pharma Technology, 2017)
Background and purpose: One way to hospital infection control, identify and determine Infection transmission tools that can be useful in the prevention. The purpose of this study was to determine the frequency and type of pollution instruments for 6 months in the treatment units. Material and method: This retrospective study was done from April to September 2014. Were taken 422 samples from disinfected instruments. Laboratory personnel were sampling with sterile swab then cultured. If bacterial was growth and creating colony examined the type of bacteria. Collected data were analyzed with descriptive statistics. Results: The results showed gram-negative from 422 cultures were done 62 cases (14.69%) were positive. the microbial strains were 4 cases gram-negative (6.45%), 4 cases (70.96%) gram-positive and 14 cases (22.58%) mixture of fungi, gram-positive. The highest contamination was in bed 21 cases (33.86%). The highest contamination was in Surgical Ward 15 case (24.19%). Hospital infection rates in the first six months were three cases of 9600 admitted patients. Conclusion: These study findings was emphasize the importance and necessity of closer and deeper attention to the infection risk factors in order to reduce and control the nosocomial infection. Despite the principles cleaning and disinfection of surfaces are standard. Keywords: Microbial contamination of hospital equipment, Nosocomial infection, Microbial contamination of hospital wards.